2022
DOI: 10.2340/17453674.2022.5276
|View full text |Cite
|
Sign up to set email alerts
|

Subtherapeutic levels of cefuroxime inside a cannulated pedicle screw used in spine surgery: results from a porcine microdialysis study

Abstract: Background and purpose: Minimally invasive spine surgery has continuously evolved for specific surgical procedures and patient populations to lower morbidity and the risk of postoperative bacterial infection. Perioperative antibiotic prophylaxis is an important preventive measure and local tissue concentrations can be quantified with microdialysis. Insertion of spinal implants induces tissue trauma and inflammation, which may affect antibiotic proximate implant concentrations. We compared perioperative cefurox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The study was reported in compliance with the ARRIVE guidelines (Percie du Sert et al, 2020) and with the recommendations made by the British Journal of Pharmacology (Lilley et al, 2020). With reference to reduction, refinement and replacement (the 3Rs) (Tannenbaum & Bennett, 2015), the pigs used in this study were also included in studies assessing cefuroxime concentrations in the anterior and posterior vertebral column of the spine and inside a cannulated pedicle screw (Hvistendahl, Bue, et al, 2022; Hvistendahl, Hanberg, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The study was reported in compliance with the ARRIVE guidelines (Percie du Sert et al, 2020) and with the recommendations made by the British Journal of Pharmacology (Lilley et al, 2020). With reference to reduction, refinement and replacement (the 3Rs) (Tannenbaum & Bennett, 2015), the pigs used in this study were also included in studies assessing cefuroxime concentrations in the anterior and posterior vertebral column of the spine and inside a cannulated pedicle screw (Hvistendahl, Bue, et al, 2022; Hvistendahl, Hanberg, et al, 2022).…”
Section: Methodsmentioning
confidence: 99%